Prevention of the Predatory Pricing Practices for Imported Products in E-Commerce - Sakti*, Muthia; Sulastri, Sulastri; Kurniawan, Itok Dwi; Putri, Fairuz Mumtaz Abafiyah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The practice of predatory pricing is a sales strategy that sets very low prices with the aim of removing competitors from the market and attracting buyers at low prices. Article 20 of the Law of the Republic of Indonesia No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition states that business actors are prohibited from supplying goods and or services by selling at a loss or setting meagre prices with the intent to eliminate or terminate the business of its competitors in the relevant market to result in monopolistic practices and or unfair business competition. The type of research that will be used to analyse problems related to the alleged practice of selling at a loss on the Shopee e-commerce site is normative juridical. The legal approach that the author will use is the statutory approach. The development of the e-commerce industry can benefit consumers and businesses. In searching for a case, 2 sources can be found by KPPU, namely based on reports and initiatives from KPPU itself. Not only that, an in-depth examination process and sufficient evidence are needed so that the case can be followed up to the next stage. Regarding preventive measures, KPPU has continued to conduct in-depth research since 2017 to be able to map the digital economic ecosystem and the potential for anti-competitive behaviour that might occur in the future in the digital era. This matter is also stated in the KPPU's Strategic Plan for 2020-2024.